2008
DOI: 10.1111/j.1547-5069.2008.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

A Causal Model of Health‐Related Quality of Life in Thai Patients With Heart‐Failure

Abstract: Background: Heart failure is an increasing global health problem which adversely affects all aspects of a patient's health-related quality of life (HRQOL). Purpose: The hypothesized causal model of HRQOL in Thai heart-failure patients was based on Wilson and Cleary's HRQOL conceptual model. We examined causal relationships among bio-physiological status, symptoms, functional status, general health perception (GHP), and HRQOL shown in the model, and added an additional item-social support. Methods: A stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
0
22
0
2
Order By: Relevance
“…The Thai version has been used in 422 HF patients and in pilot testing in a sample of 30, had good reliability (Cronbach's alpha coefficient was 0.94 (Krethong et al . ). The MLHF was applied only to patients with HF and not the carers.…”
Section: The Studymentioning
confidence: 97%
“…The Thai version has been used in 422 HF patients and in pilot testing in a sample of 30, had good reliability (Cronbach's alpha coefficient was 0.94 (Krethong et al . ). The MLHF was applied only to patients with HF and not the carers.…”
Section: The Studymentioning
confidence: 97%
“…Furthermore, it has been reported that patients experience a threat, uncertainty, and emotional instability during the stage of recovery after discharge (4). IHD and Heart failure has been pointed out to affect the quality of life of patients in the aspect of health (5,6), and thus a comprehensive symptom management and a prevention and treatment program are recognized as important. However, patient symptom management after discharge is critical since the diffusion rate of comprehensive cardiac rehabilitation is low in Japan.…”
Section: Originalmentioning
confidence: 99%
“…6 Quality of life in HF patients is decreased when compared with people with other chronic health problems and the population in general. 7 Quality of life has been increasingly recognized as a salient patient outcome to study, especially in instances of chronic illnesses such as HF, and is one of the most common health outcome measures in interventional studies with HF patients.…”
Section: Hf and Health-related Outcomesmentioning
confidence: 99%